ANALISIS PERMINTAAN IMPOR DAGING SAPI DI INDONESIA - Sintya J. K Umboh; Grando D Lumawir; Lidya Kalangi (Jambura Journal of Animal Science, 2023)
The purpose of this study was to determine the development of beef imports in Indonesia. This study uses quantitative analysis with time series data regression. Secondary data was obtained from BPS by analyzing the coefficient of determination test (R2) so that an R2 value of 0.907 was obtained. This shows that 90.7% of the demand for beef imports in Indonesia can be explained by the variables of domestic beef prices, world beef prices, exchange rates, and income per capita, while the remaining 9.3% is explained by other variables outside the model. The results of the study show that the variable price of domestic beef, variable world meat prices, variable per capita income affect the demand for beef imports in Indonesia. However, the variable exchange rate of the rupiah against the dollar has no effect on the demand for imported beef in Indonesia.